Selective Changes in Complexity of Visual Scanning for Social Stimuli in Infancy - Tomalski, Przemysław; López Pérez, David; Radkowska, Alicja; Malinowska-Korczak, Anna (Frontiers in Psychology, 2021)
In the 1st year of life, infants gradually gain the ability to control their eye movements and explore visual scenes, which support their learning and emerging cognitive skills. These gains include domain-general skills such as rapid orienting or attention disengagement as well as domain-specific ones such as increased sensitivity to social stimuli. However, it remains unknown whether these developmental changes in what infants fixate and for how long in naturalistic scenes lead to the emergence of more complex, repeated sequences of fixations, especially when viewing human figures and faces, and whether these changes are related to improvements in domain-general attentional skills. Here we tested longitudinally the developmental changes in the complexity of fixation sequences at 5.5 and 11 months of age using Recurrence Quantification Analysis. We measured changes in how fixations recur in the same location and changes in the patterns (repeated sequences) of fixations in social and non-social scenes that were either static or dynamic. We found more complex patterns (i.e., repeated and longer sequences) of fixations in social than non-social scenes, both static and dynamic. There was also an age-related increase in the length of repeated fixation sequences only for social static scenes, which was independent of individual differences in orienting and attention disengagement. Our results can be interpreted as evidence for fine-tuning of infants' visual scanning skills. They selectively produce longer and more complex sequences of fixations on faces and bodies before reaching the end of the 1st year of life.